PERNIKAHAN BEDA AGAMA (Tafsir Tematik Alquran Tentang Hubungan Sosial Antar-Umat Beragama Karya Muhammadiyah) - Maulida, Fahma; Achris Achsanudtaqwin; Rif'atur Roifah (STAI KH. Muhammad Ali Shodiq, 2023)
Interfaith marriage is no longer a new issue and is still interesting to study. This research is a type of literature research. While the research model is qualitative research and uses the comparative-analysis method for data analysis. After conducting the analysis, it was concluded that the sources of interpretation used by Muhammadiyah when interpreting the verses on interfaith marriage include: The Qur'an, hadith, companion and tabi'in narrations, reasoning (ijtihad), previous books of interpretation, and fiqh books. The method of interpretation used by Muhammadiyah is the thematic method with the style of al-A>da>b al-Ijtima>'i (social-community). While the validity of the interpretation of the verses of interfaith marriage after being tested with three theories of truth, the results are obtained: 1) According to the coherence theory, Muhammadiyah's interpretation is considered incorrect because it is inconsistent in conveying propositions through the logic of its thinking and inconsistent between the contextual approach used in the interpretation explained in the